Enhancing mobile e-book usability for the visually impaired: A novel model validated via the fuzzy delphi method - Matraf, Munya Saleh Ba; Hashim, Nor Laily; Hussain, Azham; Habbal, Adib; Hamouda, Hassen; Ghazali, Osman (Journal of King Saud University. Computer and information sciences, 2025)
Current usability evaluation models for e-books do not adequately address the needs of the visually impaired, as they require customisation to effectively evaluate these applications, considering the unique accessibility requirements of the visually impaired and the distinct features of e-books. This study presents a structured three-phase approach to developing a usability evaluation model specifically designed for mobile e-book applications used by the visually impaired. The first phase involved gathering requirements through a literature review and online survey. The second phase focused on verifying the proposed model using the Fuzzy Delphi Method. The final phase involved consolidating the verified measurements to establish the usability evaluation model. Five usability factors were identified: accessibility, satisfaction, effectiveness, learnability, and efficiency. The inclusion of accessibility ensures that the needs of the visually impaired are addressed. Besides, 31 usability metrics were validated through FDM. The findings confirm the applicability of the proposed model by demonstrating systematic expert agreement on the identified factors and metrics. The Fuzzy Delphi Method validates 31 usability metrics, thereby strengthening the reliability and applicability of HCI and accessibility research. This model promotes inclusive technology development, supporting the creation of usable and empowering e-book applications for users who are visually impaired.